The Genome Copy Number of the Thermophilic Cyanobacterium Thermosynechococcus elongatus E542 Is Controlled by Growth Phase and Nutrient Availability - Riaz, Sadaf (Appl Environ Microbiol, 2021)
The recently isolated thermophilic cyanobacterium Thermosynechococcus elongatus PKUAC-SCTE542 (here Thermosynechococcus E542) is a promising strain for fundamental and applied research. Here, we used several improved ploidy estimation approaches, which include quantitative PCR (qPCR), spectrofluorometry, and flow cytometry, to precisely determine the ploidy level in Thermosynechococcus E542 across different growth stages and nutritional and stress conditions. The distribution of genome copies per cell among the populations of Thermosynechococcus E542 was also analyzed. The strain tends to maintain 3 or 4 genome copies per cell in lag phase, early growth phase, or stationary phase under standard conditions. Increased ploidy (5.5 ± 0.3) was observed in exponential phase; hence, the ploidy level is growth phase regulated. Nearly no monoploid cells were detected in all growth phases, and prolonged stationary phase could not yield ploidy levels lower than 3 under standard conditions. During the late growth phase, a significantly higher ploidy level was observed in the presence of bicarbonate (7.6 ± 0.7) and high phosphate (6.9 ± 0.2) at the expense of reduced percentages of di- and triploid cells. Meanwhile, the reduction in phosphates decreased the average ploidy level by increasing the percentages of mono- and diploid cells. In contrast, temperature and antibiotic stresses reduced the percentages of mono-, di-, and triploid cells yet maintained average ploidy. The results indicate a possible causality between growth rate, stress, and genome copy number across the conditions tested, but the exact mechanism is yet to be elucidated. Furthermore, the spectrofluorometric approach presented here is a quick and straightforward ploidy estimation method with reasonable accuracy. IMPORTANCE The present study revealed that the genome copy number (ploidy) status in the thermophilic cyanobacterium Thermosynechococcus E542 is regulated by growth phase and various environmental parameters to give us a window into understanding the role of polyploidy. An increased ploidy level is found to be associated with higher metabolic activity and increased vigor by acting as backup genetic information to compensate for damage to the other chromosomal copies. Several improved ploidy estimation approaches that may upgrade the ploidy estimation procedure for cyanobacteria in the future are presented in this work. Furthermore, the new spectrofluorometric method presented here is a rapid and straightforward method of ploidy estimation with reasonable accuracy compared to other laborious methods.